Diagnostic value of serum TGF-β1 and CysC in type 2 diabetic kidney disease: a cross-sectional study - Kang, Yi; Jin, Qian; Zhou, Mengqi; Zheng, Huijuan; Li, Xiaobin; Li, Aoshuang; Zhou, Jing Wei; Lv, Jie; Wang, Yaoxian (Frontiers in Medicine, 2025)
BackgroundDiabetic kidney disease (DKD) is one of the common microvascular complications of diabetes. The exploration of serum biomarkers holds promise for improving the efficiency and accuracy of early DKD diagnosis. This study aims to investigate the diagnostic value of transforming growth factor-β1 (TGF-β1) and cystatin C (CysC) in DKD patients.MethodsA total of 126 patients with type 2 diabetes mellitus (T2DM) diagnosed at Dongzhimen Hospital, Beijing University of Chinese Medicine, between May 2021 and March 2023 were enrolled. Patients were categorized based on proteinuria levels and estimated glomerular filtration rate (eGFR). Correlation analyses were conducted to examine the relationships between serum TGF-β1, CysC, and clinical parameters. Logistic regression was applied to identify correlation factors for DKD and renal function impairment in T2DM patients. Furthermore, receiver operating characteristic (ROC) curve analysis was performed to assess diagnostic efficacy.ResultsSignificant differences in TGF-β1 and CysC levels were observed across groups with varying proteinuria levels. CysC was positively correlated with TGF-β1 (r = 0.640, p < 0.001). TGF-β1 has been associated with proteinuria levels in T2DM patients. Each unit increase in TGF-β1 was associated with a 1.122-fold and 1.470-fold higher odds of the presence of microalbuminuria and proteinuria, respectively, in the normal proteinuria (NP) group. TGF-β1 and CysC showed varying diagnostic performance. TGF-β1 better distinguished microalbuminuria group (MP) from NP, while CysC alone was less effective. T2DM patients with impaired renal function exhibited significantly higher CysC and TGF-β1 levels compared to those with normal renal function. CysC emerged as an associated factor of renal function decline (OR = 2.255, p = 0.008). CysC demonstrated superior diagnostic efficacy compared to TGF-β1 in predicting renal function impairment (AUC = 0.974).ConclusionCysC and TGF-β1 can serve as potential biomarkers for assessing renal impairment and proteinuria in T2DM patients. Their combined evaluation demonstrates diagnostic value and clinical application potential.